ANALISIS UJARAN KEBENCIAN BERDASARKAN UNDANG-UNDANG NOMOR 7 TAHUN 2017 TENTANG PEMILIHAN UMUM - Fitri, Elya; Yusrizal, Yusrizal; Hidayat, Hidayat (Jurnal Ilmiah Mahasiswa Fakultas Hukum Universitas Malikussaleh, 2024)
Hate speech is speech, behavior, writing, or performance that is prohibited because it can trigger violence and prejudice on the part of the perpetrator of the statement or victim. General election is an instrument to realize people sovereignty. This research is conducted in a normative juridical manner, namely examining norms when in their application there is a lack of clarity of norms, either due to the accurrence of a norm vacuum, norm vagueness, or conflict of norm by using library legal materials which include primary legal materials and secondary legal materials. The result of the research show that hate speech in law number 7 of  2017 concering general elections is regulated in article 280 paragraph (1) letter c and the legal handling of hate speech cases is not specifically regulated, therefore collaboration with regulations or laws such as the criminal code (KUHP), law number 19 of 2016 concerning information information and electronics, and generals elections election commission regulation number 15 of 2023 concering general election campaigns is required. At the end of this research, it is concluded that the main thing that causes hate speech cases to not stop during the general election periode is due to the absence of specific rules governing law number 7 on general elections related to hate speech.